2003
DOI: 10.1074/jbc.m206607200
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination and Proteasomal Degradation of Endogenous and Exogenous Inositol 1,4,5-Trisphosphate Receptors in αT3-1 Anterior Pituitary Cells

Abstract: 276, 3123-3129). In the current study, we sought to define the mechanism behind this adaptive response. We show that GnRH induces a rapid and dramatic increase in InsP 3 receptor polyubiquitination and that proteasome inhibitors block InsP 3 receptor down-regulation and cause the accumulation of polyubiquitinated receptors. Thus, the ubiquitin/proteasome pathway is active in ␣T3-1 cells, and GnRH regulates the levels of InsP 3 receptors via this mechanism. Given these findings and further characterization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 51 publications
5
89
0
Order By: Relevance
“…A similar GnRH-induced degradation of IP3 receptors has also been described [38]. In addition to such metabolic events, studies have shown that GnRH may also alter the degree of its effect on gonadotropin secretion through its multigenic regulatory action within the gonadotrophs.…”
Section: Gnrh Receptor Signallingsupporting
confidence: 53%
“…A similar GnRH-induced degradation of IP3 receptors has also been described [38]. In addition to such metabolic events, studies have shown that GnRH may also alter the degree of its effect on gonadotropin secretion through its multigenic regulatory action within the gonadotrophs.…”
Section: Gnrh Receptor Signallingsupporting
confidence: 53%
“…This lack of complete inhibition could be due to the action of residual RNF170 after RNA interference or from the activity of another ligase or other ligases. Interestingly, whereas stimulus-induced IP 3 receptor degradation was only partially blocked by RNF170 depletion in ␣T3-1 cells, it was completely blocked in mHeLa cells. This suggests that, in mHeLa cells, in addition to catalyzing IP 3 receptor ubiquitination, RNF170 may govern the activity of an additional protein, perhaps an ERAD pathway component, that is required for IP 3 receptor degradation.…”
Section: Discussionmentioning
confidence: 99%
“…FLAG Inhibits IP 3 Receptor Ubiquitination and Degradation-To assess the role of RNF170 in IP 3 receptor processing, we used RNA interference to deplete endogenous RNF170. In ␣T3-1 cells, introduction by electroporation of a vector encoding a siRNA targeting RNF170 resulted in specific depletion of RNF170.…”
Section: Depletion Of Endogenous Rnf170 or Overexpression Of *Rnf170mentioning
confidence: 99%
See 2 more Smart Citations